Knowledge, attitude and practice of nursing staff regarding hepatitis B at Kut city, middle Iraq - Rawaa Kamel Abd; Basim Rihan Sahar (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the level of knowledge, attitude and practice of nursing staff towards hepatitis B virus infection. Method: The cross-sectional study was conducted at three hospitals in Kut, Iraq, in July 2020, and comprised nursing staff regardless of age and gender. Data was collected using a predesigned questionnaire exploring demographic details as well as knowledge, attitude and practice of the nursing staff regarding hepatitis B virus infection. Data was analysed using SPSS 21. Result: Of the 3,008 nurses, 341(11.33%) were randomly enrolled; 170(49.9%) males and 171(50.1%) females. There were 140(41.1%) subjects aged 20–30 years, while 16(4.7%) were aged Greater than or Equal to 50 years. The mean knowledge score was 22.22±2.79 (range: 18-35 years), indicating better knowledge. The mean attitude score was 19.23±2.74 (range: 11-26), indicating positive attitude. The mean practice score was 13.04±1.84 (range: 8-17) indicating good practices. Conclusion: The knowledge level related to hepatitis B virus among the nursing staff was good. Overall improvement related to knowledge, attitude and practice among the nursing staff was needed. Keywords: Hepatitis, Virus, Health, Studies, Nurses, Surveys.